(Study on The Utilization of Solid Waste of Coconut Milk Process as Raw Material for Snack Foods) - Solechan -; Elly Nurlaelyah (Balai Besar Industri Agro, 1996)
The untilization of solid waste from coconut milk process and the presscake from co-extraction coconut oil process have been studied.The aim of the research was to find out the possibility of using solid waste and presscake as raw materials for biscuit making.The combination of wheat flour and solid waste or wheat flour and presscake at different percentage have been studied.The nutritient content of biscuit produced have been analysed,and the result indicated that the protein content range between 3.13% to 9.27%,the fat content between 20.01% to 48.39% and the carbohydrate content between 35.46% to 54.29%.Organoleptic test showed that the mix of 50% wheat flour and 50% solid wastes was prefertable than other combinaion